Terceirização, globalização e princípio de isonomia salarial - Melhado, Reginaldo (2018)
Submitted by rsmoira@stj.jus.br (rsmoira@stj.jus.br) on 2018-09-11T19:11:41Z No. of bitstreams: 2 terceirizacao_globalizacao_principio_melhado.pdf: 2023566 bytes, checksum: 0fd145b68054581c16c1e325b7cc97f2 (MD5) license.txt: 1239 bytes, checksum: c9b4c351324448672315a00808efb725 (MD5)